Pengaruh Iklim terhadap Kasus Dengue di Kota Bandung: 2011-2020 - Oka Septiriani; Mondastri Korib Sudaryo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Global warming has an impact on climate change causing an increase in cases of mosquito borne disease. There are several factors that influence the incidence of dengue including climate consisting of humidity, rainfall, temperature, duration of sunshine, wind speed, and number of rainy days. The occurrence of changes in climatic parameters contributes to an increase in the number of vectors, increases the life span of vectors, and expands the spread of dengue vectors. This study aims to determine the relationship between climate and dengue incidence in Bandung City for 10 years (2011-2020). This research was an analytical research that uses ecological design according to place and time. The data used were climate parameter data and dengue incidence. The incidence of dengue during 2011-2020 fluctuated. The results of statistical tests showed that there was a correlation between dengue cases with maximum temperature (r= -0.36; p-value=0.0001), humidity (r= 0.26; p-value=0.004) and maximum wind speed (r= -0.27; p-value=0.003). From the results of this study, climate parameters have an effect on increasing the incidence of dengue so that strict PSN efforts are needed, especially starting in September when dengue cases begin to increase.